Venha nos conhecer - Parras, Andrea Alves [UNESP]; Buriola, Marcelo Henrique [UNESP]; Bordignon, Leonardo Sacchi [UNESP]; Garcia, Thais Gielfi [UNESP]; Amorim, Tiago [UNESP]; Okamoto, Roberta [UNESP]; Botacin, Paulo Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Universidade Estadual Paulista - Unesp besides being a public Institution, with excellent quality and free education presents different characteristics, since it is distributed throughout the State of São Paulo. In addition to disseminating cutting-edge information, the organization is also deeply committed to promote social inclusion. This project aims to enable young people who is about to enter in higher education system, to know as actual model of free University and realize that the entry of the needing young, or not, to this Education Institution is possible and available for everyone. Through guided tours to Unesp, students of the secondary education could reflect on the importance of the choice of a profession, to know the courses offered by Unesp and in which cities these courses take place. Also they come to know how to the university and the possibilities for maintaining the student in the course.

A Universidade Estadual Paulista – Unesp além de pública, com excelente qualidade e gratuita, tem características diferentes, pois está distribuída em todo Estado de São Paulo. Além de disseminar informação de ponta, a entidade também está profundamente comprometida em favorecer a inclusão social. Este projeto visa possibilitar que os jovens, em vias de ingresso no Ensino Superior, conheçam um bom modelo de Universidade Pública, e percebam que o ingresso de jovens carentes ou não aos bancos desta instituição de ensino é possível e está ao alcance de todos. Por meio de visitas orientadas à Unesp os alunos do ensino do segundo grau, puderam refletir sobre a importância da escolha da profissão, saber quais aquelas oferecidas pelos cursos da Unesp e onde esses cursos acontecem. Também passaram a conhecer a forma de acesso e as possibilidades para a manutenção do acadêmico no curso.
Keywords: Universities; Social group; Education secondary; Universidades; Grupo social; Ensino médio